ANALISIS USAHA BUDIDAYA DAN PEMASARAN IKAN LELE DI DESA HANGTUAH (KAMPUNG LELE) KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR - Novri Arsadti; Tibrani (DINAMIKA PERTANIAN, 2024)
Agriculture, particularly the fisheries sector, plays a crucial role in Indonesia's economy. Catfish is a significant commodity that enhances the national economy and is widely appreciated by consumers. This study aims to: (1) examine the characteristics of farmer traders and the profiles of catfish farming businesses, (2) evaluate cultivation techniques, the utilization of production factors, production costs, income, and efficiency of catfish farming, and (3) investigate the use of marketing institutions and channels, as well as related costs, profit margins, farmer shares, and marketing efficiency for catfish. Conducted in Hangtuah Village (Kampung Lele), Perhentian District, Kampar Regency, this research spanned six months, from January to July 2023. Data was analyzed using descriptive qualitative and quantitative methods, utilizing both primary and secondary data sources. Findings reveal the following characteristics: farmers had an average age of 41 years,9 years of education, 7 years of farming experience, and an average of 3 dependents; collecting traders are approximately 40 years old, with 7 years of business experience, 9 years of education, and 3 family dependents; and retailers have an average age of 40 years, 6 years of business experience, 9 years of education, and 2 family dependents. The catfish farming business in tarpaulin ponds typically operates on individual land, with farmers using their own capital, starting from around IDR 10,000,000 to IDR 20,000,000. According to the research findings, farmers in Hangtuah Village implement catfish cultivation techniques were supported by theoretical frameworks, employing three types of feed: PF 1000 pellets (with an average total usage of 99 kg per production period), 781 pellets (averaging 148 kg per production period), and additional feed totaling IDR 500,000 per production period. Labor utilization among family members averaged 25.97 hours per production period, with total costs averaging around IDR 8,460,200 per production period. Additionally, the gross income for farmers engaged in catfish hatchery and rearing amounted to IDR 23,940,000 per production period, resulting in a net income of IDR 15,479,800 and a Revenue Cost Ratio (RCR) of 2.80.